Quorum Sensing Inhibitors from Marine Microorganisms and Their Synthetic Derivatives - Chen, Jianwei (Mar Drugs, 2019)
Quorum sensing inhibitors (QSIs) present a promising alternative or potent adjuvants of conventional antibiotics for the treatment of antibiotic-resistant bacterial strains, since they could disrupt bacterial pathogenicity without imposing selective pressure involved in antibacterial treatments. This review covers a series of molecules showing quorum sensing (QS) inhibitory activity that are isolated from marine microorganisms, including bacteria, actinomycetes and fungi, and chemically synthesized based on QSIs derived from marine microorganisms. This is the first comprehensive overview of QSIs derived from marine microorganisms and their synthetic analogues with QS inhibitory activity.